2019
DOI: 10.3390/cells8070698
|View full text |Cite
|
Sign up to set email alerts
|

Single Cell Gene Co-Expression Network Reveals FECH/CROT Signature as a Prognostic Marker

Abstract: Aberrant activation of signaling pathways is frequently observed and reported to be associated with the progression and poor prognosis of prostate cancer (PCa). We aimed to identify key biological processes regulated by androgen receptor (AR) using gene co-expression network from single cell resolution. The bimodal index was used to evaluate whether two subpopulations exist among the single cells. Gene expression among single cells revealed averaging pitfalls and bimodality pattern. Weighted gene co-expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 35 publications
1
18
0
Order By: Relevance
“…Establishing gene scoring models contribute to quantify the prognostic evaluation criteria and increasing studies have performed successful precedents in this regard. [ 12 , 15 , 16 ] Our current study established a six-gene prognosis predictive model in patients with PaCa and validated the prognostic value of this model in total PaCa patients and several subgroups, confirming that the six-gene prognosis model could exactly predict the OS of patients with PaCa.…”
Section: Discussionsupporting
confidence: 66%
“…Establishing gene scoring models contribute to quantify the prognostic evaluation criteria and increasing studies have performed successful precedents in this regard. [ 12 , 15 , 16 ] Our current study established a six-gene prognosis predictive model in patients with PaCa and validated the prognostic value of this model in total PaCa patients and several subgroups, confirming that the six-gene prognosis model could exactly predict the OS of patients with PaCa.…”
Section: Discussionsupporting
confidence: 66%
“…For example, WGCNA along with scRNA-seq data from early embryo cells revealed that each stage of the early development of mouse and human embryos can be delineated by a few functional modules 59 . WGCNA on single-cell transcriptome data also enabled the discovery of signals that activate dormant neural stem cells in nonneurogenic brain regions 60 , regulators of chemotherapy resistance in esophageal squamous cell carcinoma 61 and prognostic markers for prostate cancer 62 . The WGCNA package requires users to adjust various parameters so that appropriate modules are defined, and this may often become a potential difficulty in the absence of prior knowledge of disease-associated gene sets.…”
Section: Hypothesis From Subnetwork Analysismentioning
confidence: 99%
“…Newly emergent single-cell technologies hold the key to profiling the vast heterogeneous landscapes of prostate cancer [8,[14][15][16][17][18][19]. Recently, whole genomes of 20 single cells from localized prostate tumors were sequenced [20], revealing significant cell-to-cell variation in mutations and complex subclonal trajectories.…”
Section: Introductionmentioning
confidence: 99%